Pain Sensitisation in Women with Active Rheumatoid Arthritis: A Comparative Cross-Sectional Study. (21st July 2015) - Vladimirova, Nora; Jespersen, Anders; Bartels, Else Marie; Christensen, Anton W.; Bliddal, Henning; Danneskiold-Samsøe, Bente
Abstract : Objectives . In some rheumatoid arthritis (RA) patients, joint pain persists without signs of inflammation. This indicates that central pain sensitisation may play a role in the generation of chronic pain in a subgroup of RA. Our aim was to assess the degree of peripheral and central pain sensitisation in women with active RA compared to healthy controls (HC). Methods . 38 women with active RA (DAS28 > 2.6 ) and 38 female HC were included in, and completed, the study. Exclusion criteria were polyneuropathy, pregnancy, and no Danish language. Cuff Pressure Algometry measurements were carried out on the dominant lower leg. Pain threshold, pain tolerance, and pain sensitivity during tonic painful stimulation were recorded. Results . Women with active RA had significantly lower pain threshold (p < 0.01 ) and pain tolerance (p < 0.01 ) than HC. The mean temporal summation- (TS-) index in RA patients was 0.98 (SEM: 0.09) and 0.71 (SEM: 0.04) in HC (p < 0.01 ). Conclusion . Patients with active RA showed decreased pressure-pain threshold compared to HC. In addition, temporal summation of pressure-pain was increased, indicating central pain sensitization, at least in some patients. Defining this subgroup of patients may be of importance when considering treatment strategies.